Evaluation of soft tissue simulant performance against economic and environmental impact - Read, James; McNaught, Ken R.; Hazael, Rachael; Critchley, Richard (Royal Society of Chemistry (RSC), 2024)
Soft tissue simulants are traditionally used to provide a post impact medium suitable for replicating human anatomy. Performance of materials is therefore paramount, and the analysis of such experimentation relies on responses that mimic the various tissue, bone and muscle groups contained within the human body. However, with an increasing global push to reduce carbon emissions and increase sustainability, current materials require examination to ensure research establishments remain at the forefront of environmentally friendly practices. To date, the literature contains little in relation to how environmentally friendly the use and supply of soft tissue simulants is. The aim of the research is to provide researchers with primary data to support decisions on material selection for ballistic simulation research. The need arises due to the high cost and environmental impact of existing materials. To explore this research gap, a series of 5.5 mm ball bearings were fired from a gas gun at velocity ranges between 122 and 526 m s−1 to examine the performance characteristics of six commercially available soft tissue simulants and a foodstuffs grade gelatine that represented a more cost effective environmentally friendly alternative. A structured multi-criteria decision analysis approach was employed to compare the overall effectiveness of the alternative materials. It was found that whilst PermaGel, 20 and 10% ballistic gelatine performed the most advantageously respectively during experimental testing, qualitative environmental assessment showed ballistic soap, PermaGel and foodstuffs gelatine to be most advantageous. The information provided within this study will enable researchers to make more informed decisions on both economic and environmental implications when sourcing materials for use within survivability assessment, whilst further work would increase awareness and viability of alternative materials.